A Rare Case Series of Ischemic Stroke Following Russell's Viper Snake Bite in India - Venkata Krishna Pothukuchi; Alok Kumar; Chennamsetty Teja; Archana Verma (Interna Publishing, 2018)
Snakebite is an important medical problem in India. Among their various manifestations, cerebral complications are uncommonly found in literature. Moreover, Ischemic stroke following snake bite is quite rare. Here we report a case series of two such cases that developed neurological manifestations following Russell's viper bite. On computerized tomography (CT) scan of brain; cerebral infarcts were revealed. Their likely mechanisms are discussed in present study which include disseminated intravascular coagulation, toxin induced vasculitis and endothelial damage.